Proceedings - 2012 3rd IEEE International Symposium on Power Electronics for Distributed Generation Systems, PEDG 2012 - Mokhtari, G.; zare, F.; Nourbakhsh, G.; Ghosh, Arindam (-, 2012)
Given the paradigm of smart grid as the promising backbone for future network, this paper uses this paradigm to propose a new coordination approach for LV network based on distributed control algorithm. This approach divides the LV network into hierarchical communities where each community is controlled by a control agent. Different level of communication has been proposed for this structure to control the network in different operation modes.